FAKTOR-FAKTOR PENGHAMBAT DALAM PROSES PELAKSANAAN JAMINAN PERSALINAN (JAMPERSAL) DI DESA SIMPANG KANAN KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Uswetun Hasanah E.01109053 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Implementation of the Childbirth Insurance program in Village Simpang Kanan Sub-district Sungai Ambawang Regency Kubu Raya is still effectiveless because there are some factors that influence in implementation process of the Childbirth Insurance program. The problems in the implementation of the Childbirth Insurance program that lack of information distribution and luck or equipment resources to implement the Childbirth Insurance program in Village Simpang Kanan Sub-district Sungai Ambawang Regency Kubu Raya. Through this article that aims to make the implementation of the Childbirth Insurance program in Village Simpang Kanan Sub-district Sungai Ambawang continue to be implemented effectively, so that people or pregnant women is submissive and willing to follow the Childbirth Insurance program. The method that is used is descriptive method with qualitative data analysis . The results of research that there are still pregnant womens who do not know about the existence of the Childbirth Insurance program and lack availability of medical equipment in Village Simpang Kanan health post such as there is no tool to check, weight scales, drugs,bed and other equipment that is available only chairs, tables and cupboard that are not neat . with thus is expected in order that the implementation of the Childbirth Insurance program in Village Simpang Kanan Sub-district Sungai Ambawang Regency Kubu Raya can run effectively. Keywords: Childbirth Insurance Program Implementation, lack of information distribution, inadequate health facilities.